Radiation Oncology - Belka, Claus; Bert, Christoph; Combs, Stephanie; Habermehl, Daniel; Lauber, Kirsten; Nachbichler, Silke; Niyazi, Maximilian; Parodi, Katia; Roeder, Falk; Zitzelsberger, Horst; Camphausen, Kevin; Ghadjar, Pirus; et al.
Radiation Oncology encompasses all aspects of research that impacts on the treatment of cancer using radiation. It publishes findings in molecular and cellular radiation biology, radiation physics, radiation technology, and clinical oncology. The field of radiation oncology covers the integration of radiation therapy into multimodal treatment approaches. Radiation Oncology provides an open access forum for researchers and clinicians involved in the management and treatment of cancer patients, bringing together the latest research and advances in the field. Advances in treatment technology, as well as improved understanding of the underlying biological resistance mechanisms, will further strengthen the role of radiation oncology.